Influence of the Shape of Initial Imperfections on Single Web and Flange Steel Plates at Elevated Temperatures. Issue 4 (14th September 2022) - Possidente, Luca; Tondini, Nicola
Abstract: In the last decades the buckling of steel members in fire has attracted the attention of the scientific community, but considerations about the choice of the initial imperfections have been rarely the focus of scientific publications. However, initial imperfections play a primary role in the definition of the resistance, especially when local buckling is investigated. Although the lowest buckling mode is usually employed, the definition of an appropriate imperfection shape providing, for instance, the lowest resistance is not straightforward. Even more so when the local behaviour at elevated temperatures is being studied, since the buckling behaviour may differ from the one at ambient temperature, owing to the steel degradation and possible load redistributions. In this paper steel plates in compression at elevated temperatures are studied considering different shapes of imperfection. A parametric analysis on webs and flanges composing Class 4 HE and IPE sections with S355 steel grade is presented, considering five temperatures in a relevant range (400–800°C) and several plate aspect ratios. The influence of the imperfection shapes on the resistance depending on the temperature, the length and the slenderness of the web and flange plates is discussed.